2017
DOI: 10.21608/ejom.2017.960
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual Syndrome and Work Among Female Academic Teaching Staff in Agovernmental Faculty of Medicine in Egypt

Abstract: Introduction: Premenstrual syndrome (PMS) affects many women during their work life. PMS in working' Egyptian women, however, are less well researched. Aim of work: To determine the prevalence of PMS in a sample of academic female teaching staff in Zagazig University and explore PMS in the work context. Materials and methods: One hundred and eighty six academic female from Zagazig University (mean age=30.74 years) participated in a comparative cross-sectional study involving a semistructured interview and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…PMS detrimentally affects an individual's quality of life. It has been shown to have an impact on all aspects of a woman's life, including daily activity, social life, study, and work productivity [ 3 , 8 , 19 ]. Our findings back up what others have discovered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PMS detrimentally affects an individual's quality of life. It has been shown to have an impact on all aspects of a woman's life, including daily activity, social life, study, and work productivity [ 3 , 8 , 19 ]. Our findings back up what others have discovered.…”
Section: Discussionmentioning
confidence: 99%
“…A key aspect of PMS is that the timing and intensity of the symptoms may be severe enough to interfere with regular daily activities. [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey of 264 females involved in academic teaching showed that the effect of premenstrual symptoms on work capacity, worsening by severity of symptoms at work, and job performance was significantly different between PMS and non-PMS women. Even 50% of the subjects found that their relationship with their colleagues was disturbed due to premenstrual symptoms (13). A study of 134 nurses in Turkey found that nurses with PMS had International Journal of Reproductive BioMedicine PMS and women's work performance a significantly lower work-related quality of life (3).…”
Section: Discussionmentioning
confidence: 99%